Local delivery of corticosteroids in clinical ophthalmology: A review. (22nd January 2020) - Fung, Adrian T.; Tran, Tuan; Lim, Lyndell L.; Samarawickrama, Chameen; Arnold, Jennifer; Gillies, Mark; Catt, Caroline; Mitchell, Logan; Symons, Andrew; Buttery, Robert; Cottee, Lisa; Tumuluri, Krishna; et al.
Abstract: Locally administered steroids have a long history in ophthalmology for the treatment of inflammatory conditions. Anterior segment conditions tend to be treated with topical steroids whilst posterior segment conditions generally require periocular, intravitreal or systemic administration for penetration. Over recent decades, the clinical applications of periocular steroid delivery have expanded to a wide range of conditions including macular oedema from retino‐vascular conditions. Formulations have been developed with the aim to provide practical, targeted, longer‐term and more efficacious therapy whilst minimizing side effects. Herein, we provide a comprehensive overview of the types of periocular steroid delivery, their clinical applications in ophthalmology and their side effects.